Branching habit as a yield determinant in cassava - Lian, Tan Swee; Cock, James H. (Elsevier, 1979)
Cassava was grown in the field and the ability of the roots to accept extra carbohydrate and the effects of branching habit on yield were observed. Apex and root were competing sinks; roots accepted more carbohydrate than was available in normal situations. Reduced sink did not limit total growth. Yield was increased by 75% by branch control. Good yields can be obtained by either late-branching types or continuous branching types with two branches at each branch level. Late-branching types appear to be the easiest to obtain in a breeding program.